2001
DOI: 10.1073/pnas.031584698
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Epstein-Barr virus (EBV) oriP-based episomes requires EBV-encoded nuclear antigen-1 chromosome-binding domains, which can be replaced by high-mobility group-I or histone H1

Abstract: EBV-encoded nuclear antigen-1 (EBNA-1) binding to a cis-acting viral DNA element, oriP, enables plasmids to persist in dividing human cells as multicopy episomes that attach to chromosomes during mitosis. In investigating the significance of EBNA-1 binding to mitotic chromosomes, we identified the basic domains of EBNA-1 within amino acids 1-89 and 323-386 as critical for chromosome binding. In contrast, the EBNA-1 C terminus (amino acids 379 -641), which includes the nuclear localization signal and DNAbinding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 29 publications
2
56
0
Order By: Relevance
“…We generated plasmids encoding these fusion proteins (p4880-H1 and p4881-LANA1(1–22) respectively), the OriP portion of the EBV genome and a gene encoding resistance to hygromycin (Figure 1C). Both the H1/EBNA1-DBD and the LANA1:1–22/EBNA1-DBD fusion proteins lack any AT-hook DNA-binding domain, but we confirmed previous results showing that both are able to maintain EBV-derived plasmids in 293 cells in the presence of selection, as are 293 cells harboring the parental p294-wtEBNA1 (Figure 1D) [20], [29]. …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…We generated plasmids encoding these fusion proteins (p4880-H1 and p4881-LANA1(1–22) respectively), the OriP portion of the EBV genome and a gene encoding resistance to hygromycin (Figure 1C). Both the H1/EBNA1-DBD and the LANA1:1–22/EBNA1-DBD fusion proteins lack any AT-hook DNA-binding domain, but we confirmed previous results showing that both are able to maintain EBV-derived plasmids in 293 cells in the presence of selection, as are 293 cells harboring the parental p294-wtEBNA1 (Figure 1D) [20], [29]. …”
Section: Resultssupporting
confidence: 90%
“…Interestingly, we and others have shown that the entire N-terminal half of EBNA1 can be replaced by proteins with or without AT-hook DNA-binding domains that maintain EBV-derived plasmids [20],[28],[29]. These seemingly contradictory findings together indicate an EBNA1-fusion protein must be able to bind mitotic chromosomes by some means in order to maintain EBV-derived plasmids in cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EBNA-1/oriP association permits the persistence of plasmids in actively dividing human cells as multicopy episomes that attach to chromosomes during mitosis [34,35]. After multiple cell divisions, oriP/EBNA-based vectors are progressively lost from the targeted host cells.…”
Section: Part 1 Recent Updates In Ipsc Generationmentioning
confidence: 99%
“…EBNA1 is a nuclear phosphoprotein which binds to the latent viral DNA replication origin and is responsible for maintenance of the viral genome in the EBV-positive cells after cell division [3234]. EBNA1, LMP1, and LMP2A have earlier been shown to promote EMT [17, 35, 36].…”
Section: Introductionmentioning
confidence: 99%